1994
DOI: 10.1051/kmae:1994005
|View full text |Cite
|
Sign up to set email alerts
|

Anguilles estuariennes et fluviales : apports de l'otolithométrie

Abstract: RÉSUMÉDes prélèvements d'anguilles (Anguilla anguilla) femelles ont été effectués dans les bassins versants de la Vilaine (n = 569) et de la Loire (n = 221), en zone fluviale et dans les deux estuaires. Les otolithes ont été poncés suivant le plan sagittal et le patron d'agencement des lignes d'arrêt de croissance (LAC) révélées par coloration au bleu de toluidine a été étudié avec une attention particulière pour l'origine fluviale ou estuarienne des échantillons. Pour une même classe de taille des poissons, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…1995) but they failed in separating the effects of latitude and habitat. Previous work that focused on a single catchment at a time, as in the Gironde Garonne Dordogne catchment (Daverat & Tomas 2006) and in the Vilaine catchment (Mounaix & Fontenelle 1994), also concluded that growth was faster in the estuary rather than upstream in the catchment.…”
Section: Discussionmentioning
confidence: 99%
“…1995) but they failed in separating the effects of latitude and habitat. Previous work that focused on a single catchment at a time, as in the Gironde Garonne Dordogne catchment (Daverat & Tomas 2006) and in the Vilaine catchment (Mounaix & Fontenelle 1994), also concluded that growth was faster in the estuary rather than upstream in the catchment.…”
Section: Discussionmentioning
confidence: 99%
“…(2003) and Daverat & Tomas (2006), conditions in coastal and estuarine brackish waters lead to a higher and more constant eel growth than straight riverine reaches. Indeed, estuaries are generally highly productive, and in addition, offer buffered conditions, especially in terms of temperature (Mounaix & Fontenelle 1994; Morrison & Secor 2003; Daverat et al. 2006; Costa et al.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the body condition revealed that eels were relatively fatter in the lower reaches of the study area which was located in the tidal freshwater zone of the estuary, whereas segments B and C were outside tidal influence. According to Mounaix & Fontenelle (1994), Acou et al (2003) and Daverat & Tomas (2006), conditions in coastal and estuarine brackish waters lead to a higher and more constant eel growth than straight riverine reaches. Indeed, estuaries are generally highly productive, and in addition, offer buffered conditions, especially in terms of temperature (Mounaix & Fontenelle 1994;Morrison & Secor 2003;Costa et al 2008).…”
Section: Longitudinal Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, marine and estuarine eels tend to grow faster than river eels (Fernandez-Delgado et al 1989, Mounaix & Fontenelle 1994, Tzeng et al 2003, Arai et al 2004, Jessop et al 2004. The drivers of these divergent life histories are still poorly understood.…”
Section: Discussionmentioning
confidence: 99%